Vaccine hesitancy and bone health: Musculoskeletal sequelae of vaccine-preventable diseases - Shabbir, Roban; Shabbir, Zubair; Parente, Paulo E.L.; Azad, Ali (Osteoporosis and Sarcopenia, 2025)
Vaccine hesitancy threatens global health by diminishing herd immunity and permitting the return of vaccine-preventable diseases (VPDs) including poliomyelitis, measles and coronavirus disease 2019 (COVID-19). These infections carry short-term and long-term musculoskeletal consequences, such as paralysis, limb deformities, septic or reactive arthritis, osteomyelitis and chronic pain, that place an ever increasing burden on orthopaedic services. This narrative review synthesizes clinical and epidemiological evidence linking sub-optimal immunization to orthopaedic morbidity caused by major VPDs. Outbreak data show that low vaccination coverage precipitates spikes in invasive bacterial disease after varicella, post-polio deformities, tetanus-related fractures, rubella-associated arthritis and COVID-19-related avascular necrosis (AVN). This impact is amplified in rapidly ageing regions such as Asia, where the population ≥ 60 years will nearly double by 2050, significantly increasing the prevalence of sarcopenia and osteoporosis that exacerbate VPD complications. Although orthopaedic surgeons are not primary vaccinators, they routinely manage these downstream effects and hold a trusted position in society from which they are able to strongly advocate for immunization. Integrating brief vaccine counselling, perioperative vaccination checks, and public health initiatives into orthopaedic practice can improve uptake and reduce preventable disability. Strengthening immunization programs and countering hesitancy are essentially critical not only for infection control but also for safeguarding a rapidly declining global musculoskeletal health. A coordinated strategy involving public-health authorities, primary-care providers, and specialists, including orthopaedic surgeons, is essential to mitigate vaccine hesitancy and its orthopaedic sequelae.